(untitled) (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVE: characterize the hospital morbidity of adults living in the city of Maringá, PR, Brazil, between 2000 and 2011, focusing on the differential between men and women. METHOD: this descriptive study was developed based on data from the Hospital Information System of the Unified Health System in order to investigate the association between groups of hospitalization causes and the average length of hospitalization per gender, in three-year periods. RESULTS: the main groups of hospitalization causes for men were: mental disorders, lesions and circulatory diseases; and, among women: tumors, circulatory and genitourinary diseases. Mental disorders and lesions, tumors, circulatory and genitourinary diseases were significantly associated with the female and male genders across the study period. Although not significant, the mean length of hospitalization dropped across the four three-year periods, and only showed a significant difference between men and women in the second triennium. CONCLUSION: differences in the hospital morbidity profile between men and women underline the need for specific health and nursing actions, especially in primary health care, with a view to reducing hospitalizations due to the main groups of causes in the city.